1997
DOI: 10.2172/554809
|View full text |Cite
|
Sign up to set email alerts
|

Radium separation through complexation by aqueous crown ethers and ion exchange or solvent extraction

Abstract: The effect of three water-soluble, unsubstituted crown ethers (1 5-crown-5 (1 5C5), 18-crown-6 (18C6) and 21-crown-7 (21C7)) on the uptake of Ca, Sr, Ba and Ra cations by a sulfonic acid cation exchange resin, and on the extraction of the same cations by xylene solutions of dmonylnaphthalenesulfonic acid (HDNNS) from aqueous hydrochloric acid solutions has been investigated. The crown ethers enhance the sorption of the larger cations by the ion exchange resin, thereby improving the resin selectivity over calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…11,17,38 (In fact, the aqueous solubility of unfunctionalized crown ethers has led to their use in several different separation schemes. [39][40][41][42] ) Similar studies have employed the more organophilic dibenzo-18-crown-6 (DB18C6, Figure 2) with HTTA in o-dichlorobenzene for partitioning of Ba(II), again for analytical purposes. 36 Cobalt(II) is the best characterized among the transition metals, 20,43 while Mn(II), 44 Zn(II), 45 Cd(II), 45 and Pb(II) 46 have also been examined using combinations of DB18C6 and HTTA for analytical separations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…11,17,38 (In fact, the aqueous solubility of unfunctionalized crown ethers has led to their use in several different separation schemes. [39][40][41][42] ) Similar studies have employed the more organophilic dibenzo-18-crown-6 (DB18C6, Figure 2) with HTTA in o-dichlorobenzene for partitioning of Ba(II), again for analytical purposes. 36 Cobalt(II) is the best characterized among the transition metals, 20,43 while Mn(II), 44 Zn(II), 45 Cd(II), 45 and Pb(II) 46 have also been examined using combinations of DB18C6 and HTTA for analytical separations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several detailed separation schemes using the solvent extraction approach 41,42 or a sulfonic acid cation-exchange resin are presented. 40,42 In a study of Eu(III) extraction by HDNNS, the addition of DCH18C6, DB24C8, or TOPO was found to have antagonistic effects. 139 By contrast to the previously discussed works in which HDDNS micelles facilitated extraction, submillimolar benzene solutions of HDNNS were employed in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[6,7] In the H 2 DEH[MDP]=o-xylene system, in contrast, addition of 21C7 leads to strong antagonistic effects for all cations except Ca 2þ . [6,7] In the H 2 DEH[MDP]=o-xylene system, in contrast, addition of 21C7 leads to strong antagonistic effects for all cations except Ca 2þ .…”
Section: Marcel Dekker Inc • 270 Madison Avenue • New York Ny 10016mentioning
confidence: 99%
“…For systems involving the use of an acidic extractant (e.g., b-diketones, carboxylic and organophosphorus acids), this is accomplished by the extractant itself, which is anionic under appropriate aqueous phase conditions. [6][7][8][9][10] Two useful insights have emerged from this work. While each of these approaches offers certain advantages, each is also subject to significant limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation